Measuring Teacher Buy-in for the Texas Pay-for-Performance Program - Lee, Jaehoon; Strong, Michael; Hamman, Doug; Zeng, Yifang (Frontiers in Education, 2021)
Teacher buy-in is a critical component for the success of any educational reform, especially one involving evaluation and compensation. We report on an instrument developed to measure teacher buy-in for district-developed designation plans associated with a state pay-for-performance (PFP) program, and teacher responses. We used modern test theory to investigate the instrument’s psychometric properties, a procedure often missing from research reports of self-designed surveys. A sample of 3,001 elementary, middle school, and high school teachers in Texas school districts participated in the survey. Our results suggest satisfactory reliability of the instrument and adequate discriminant validity in measuring distinct but related aspects of teacher buy-in. In addition, we found that teacher support for PFP as instantiated in their particular districts was generally high, but still buy-in levels varied significantly among different teacher groupings, pointing the way for future developers of pay-for-performance schemes to improve or maximize their acceptance.